Implementasi Strategi Pengembangan Sumber Daya Manusia di Industri Media Persada TV Lamongan - A. Fikri Amiruddin Ihsani Ahmad; Novi Febriyanti (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
This research discusses the implementation of human resource development strategies in the Persada TV Lamongan media industry. The purpose of this research is to describe, explain and know the implementation of human resource development strategies in the Persada TV media industry as well as to describe, explain and find out human resource development strategies in the Persada TV Lamongan media industry in a review of organizational culture theory. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were observation and documentation. The results of observations and documents that have been collected are then analyzed, compared and combined to form a systematic, coherent and complete study result. In this research, it is found that; (1) the human resource development strategy in Persada TV media begins with the procurement of manpower or human resources, development, education and training, compensation and integration aimed at utilizing employees to be willing to work hard and participate actively in supporting the achievement of Persada TV goals and fulfill the needs of employees. (2) In the review of organizational culture theory, there are elements that form culture in Persada TV, including the basic assumptions embedded in the vision and mission, values and symbols attached to the logo which are the manifestation of sowing mercy for the people by utilizing technology.